Purpura Fulminans: A Case Report and Review of All Causes. Issue 2 (March 2017) - Shenoy, Rahul; Nanjappa, Sowmya; Eaton, Kevin; Prieto-Granada, Carlos; Messina, Jane L.; Greene, John N.
Abstract : Abstract: Purpura fulminans is a rapidly progressing clinical syndrome of hematologic and cutaneous manifestations accompanied by an underlying dysfunction of coagulation resulting in disseminated diathesis. It usually occurs secondary to severe infection, but can also have an idiopathic genesis. A unique subset of inherited coagulation defects leading to fulminant purpura in neonates has also been well documented. We present a case of an adult with sarcomatoid mesothelioma on chemotherapy who presented with rapidly evolving purpuric lesions associated with acral gangrene after a recent dog bite. Once an infectious cause was ruled out, a paraneoplastic presentation of purpura fulminans secondary to the underlying malignancy was postulated. This presentation could be triggered by an altered immune system response to the preexisting neoplasm. We also discuss a comprehensive literature review of the infectious and noninfectious conditions associated with fulminant purpura. Abstract : Infectious and acquired or inherited defects in coagulation systems have been well documented to lead to fulminant purpura. This case demonstrates a rare cause of fulminant purpura associated with a paraneoplastic syndrome in a patient with mesothelioma who was receiving chemotherapy.